Early Clinical Predictors of Autism Spectrum Disorder in Infants with Tuberous Sclerosis Complex: Results from the EPISTOP Study - Moavero, Romina; Benvenuto, Arianna; Emberti Gialloreti, Leonardo; Siracusano, Martina; Kotulska, Katarzyna; Weschke, Bernhard; Riney, Kate; Jansen, Floor E; Feucht, Martha; Krsek, Pavel; Nabbout, Rima; Jansen, Anna C; et al. (Journal of clinical medicine, 2019)
Autism spectrum disorder (ASD) is highly prevalent in subjects with Tuberous Sclerosis Complex (TSC), but we are not still able to reliably predict which infants will develop ASD. This study aimed to identify the early clinical markers of ASD and/or developmental delay (DD) in infants with an early diagnosis of TSC. We prospectively evaluated 82 infants with TSC (6-24 months of age), using a detailed neuropsychological assessment (Bayley Scales of Infant Development-BSID, and Autism Diagnostic Observation Schedule-ADOS), in the context of the EPISTOP (Long-term, prospective study evaluating clinical and molecular biomarkers of EPIleptogenesiS in a genetic model of epilepsy-Tuberous SclerOsis ComPlex) project (NCT02098759). Normal cognitive developmental quotient at 12 months excluded subsequent ASD (negative predictive value 100%). The total score of ADOS at 12 months clearly differentiated children with a future diagnosis of ASD from children without (p = 0.012). Atypical socio-communication behaviors (p < 0.001) were more frequently observed than stereotyped/repetitive behaviors in children with ASD at 24 months. The combined use of BSID and ADOS can reliably identify infants with TSC with a higher risk for ASD at age 6-12 months, allowing for clinicians to target the earliest symptoms of abnormal neurodevelopment with tailored intervention strategies.
Keywords: risk factors; intellectual disability; autism; treatment; developmental delay; EPISTOP; epilepsy; diagnosis; tuberous sclerosis complex; markers